Inovasi Pembelajaran Bahasa Arab untuk Mengoptimalkan Pembelajaran di Sekolah Dasar - Fitriani, Finy; Prastowo, Andi (Study Program of Arabic Language Teaching, 2022)
Arabic is the language of the Qur'an that is important to learn, therefore in optimizing Arabic learning activities it is necessary to have learning innovations by teachers to create effective learning. The use of appropriate methods, systems, and principles to achieve learning objectives is very much needed. The purpose of this study was to determine the innovation of Arabic learning in optimizing effective learning. The method used in this study is a library research method, namely research based on the opinions of experts about Arabic learning innovations. Sources of data used are articles and journals. Data collection techniques by reading and reviewing literature and library materials that are relevant to the problem under study are Arabic learning innovations to optimize effective learning. The results of this study are that in Arabic learning innovation to optimize effective learning, it is necessary to have learning media that is by the subject matter, besides that it also requires methods, strategies, and principles so that what you want to convey can be easily accepted by students so that the creation of learning that is by the learning objectives.